El lèxic català i castellà en els escolars valencians de 3r d’educació primària. Caracterització des de la disponibilitat lèxica - Gómez-Devís, Begoña (Studia Romanica Posnaniensia, 2025)
We are interested in the initial stages of vocabulary acquisition in L1 and L2 ‒ coofficial languages ‒ and we analyze the lexical materials provided by 200 Valencian 3rd grade primary school students. The general purpose is to present the available lexical repertoires in order to discover the lexical variation ‒ Catalan and Spanish ‒ in 15 centers of interest from the quantitative results (total number of words, total number of vowels or different words, average per schoolchild) and qualitative results, analysis of the common or exclusive lexis among the 50 words that have achieved the highest index of availability in each notional area. The scope and novelty of the research lies in two essential aspects for applied linguistics in general and didactics in particular. The planning of lexical acquisition in education must be supported by research that optimizes gradual sequencing according to the maturity and linguistic competence of the students and, on the other hand, the selection of lexical materials must consider a reference lexicon based on corpora of native speakers. In other words, the specificity of this case of lexical variation is explained by its interlinguistic condition ‒ curricular training of co-official languages ‒ and school context at the initial stage of acquisition.